2021
DOI: 10.1111/jmft.12485
|View full text |Cite
|
Sign up to set email alerts
|

Equine‐assisted psychotherapy with traumatized couples—Improvement of relationship quality and psychological symptoms

Abstract: Many traumatised individuals suffering from deployment related PTSD report severe problems in their relationships. Up until now, the therapeutic interventions used by the German Armed Forces have rarely targeted these problems through the integration of partners. For this reason, a Program designed specifically for couples was developed. In this prospective study equine‐assisted psychotherapy was applied to soldiers and their spouses. The study population consisted of n = 36 couples, divided in n = 20 therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Results suggest that equine-assisted services (EAS) may be beneficial to military families; however, the number of articles is limited, and further research is needed. The current literature suggests improvements to interpersonal relationships such as reduced relationship problems, improved relationship quality and improved communication ( 40 ). Additionally, the literature suggests potential mental health benefits including reduction of depressive symptoms, somatic symptoms, and PTSD symptoms ( 35 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results suggest that equine-assisted services (EAS) may be beneficial to military families; however, the number of articles is limited, and further research is needed. The current literature suggests improvements to interpersonal relationships such as reduced relationship problems, improved relationship quality and improved communication ( 40 ). Additionally, the literature suggests potential mental health benefits including reduction of depressive symptoms, somatic symptoms, and PTSD symptoms ( 35 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The current literature suggests improvements to interpersonal relationships such as reduced relationship problems, improved relationship quality and improved communication ( 40 ). Additionally, the literature suggests potential mental health benefits including reduction of depressive symptoms, somatic symptoms, and PTSD symptoms ( 35 , 40 ). Qualitative findings suggest horses may act as a catalyst for emotional rehabilitation and healing and suggest social validity of the intervention ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the scientific literature, many studies can be found on the positive effects of AAS on humans of different ages and different diagnoses [ 27 , 28 , 29 , 30 , 31 ]. What we know less about is what the positive experiences are for the animals.…”
Section: Animal Welfare In Aasmentioning
confidence: 99%